Social psychology - Myers, David G. (McGraw-Hill, 2013)
David Myers' Social Psychology continues to set the standard by which other Social Psychology texts are judged. Its renowned author's engaging writing style and unique, intimate voice make the text compelling without being simplistic. The organization logically moves the student through the study of how people think about, influence, and relate to one another, with an appropriate balance of basic research and application